PENGARUH PENGETAHUAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (PBB) PADA KANTOR BADAN PENDAPATAN DAERAH (BAPENDA) KOTA PEKANBARU - Romadina Permatasari; Gusnardi Gusnardi; RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: The purpose of this study is to obtain an overview of the influence of knowledge and awareness of taxpayers on taxpayer compliance in paying land and building tax (PBB). This type of research is descriptive research. The population in this study are all land and building taxpayers registered at the Office of the Regional Revenue Agency (BAPENDA) in Pekanbaru in 2018, which is 121,164 taxpayers. The primary data sources were obtained directly from the selected respondents and secondary data sources from the offices of the Pekanbaru City Revenue Agency. The method of analysis uses multiple regression analysis. The variables in this study were measured using a Likert scale. To fulfill the assumption in the use of multiple regression, the data is changed to the interval scale by using Microsoft Excel. This analysis is used for research that has more than one independent variable, is used also to process and discuss the data that has been obtained, and to test the proposed hypothesis. The results of the study concluded that the knowledge and awareness of taxpayers had a significant effect on the compliance of Land and Building Taxpayers at the Office of the Regional Revenue Agency (BAPENDA) of the city of Pekanbaru. This means that if a person or taxpayer understands and has knowledge and is aware of his tax rights and obligations so that he will fulfill his obligations. Good knowledge and awareness will help and facilitate taxpayers in carrying out tax obligations. The better knowledge and awareness of taxpayers, the compliance of Land and Building Taxpayers in the Regional Office of the Regional Revenue Agency (BAPENDA) of Pekanbaru city will increase. The more obedient taxpayers in fulfilling their tax obligations will result in increasing state revenues from this sector. Key Words: Knowledge, awareness and tax compliance.